PENGARUH SIKAP, NORMA SUBJEKTIF, DAN EFIKASI DIRI TERHADAP INTENSI BERWIRAUSAHA MAHASISWA MAGISTER MANAGEMENT (KAJIAN EMPIRIS PADA SEBUAH UNIVERSITAS NEGERI - Agung Wahyu Handaru (Jurnal Universitas Paramadina, 2014)
AbstractStudy among 112 Master degree students at Faculty of Economics, State  University of Jakarta revealed some important findings: 1) students’ positive attitude is strong, students’ subjective norms is high, students’  selfefficacy is medium, and students’ entrepreneurial intention rate is  medium; 2) attitude which controlled by age significantly influenced the  students’ entrepreneurial intention; 3) subjective norms which controlled by  age significantly influenced the students’ entrepreneurial intention; 4)  selfefficacy which controlled by the age significantly influenced the  students’ entrepreneurial intention; and 5) attitude, subjective norms, and  self-efficacy which controlled by the age influenced students’  entrepreneurial intention. Another important finding shows that 14.6%  students’ entrepreneurial intention formed by attitude, subjective norms, and self-efficacy.